ASSESSMENT OF THE LEVEL OF READINESS OF TEACHING STAFF TO IMPLEMENT INNOVATIVE FORMS OF OLYMPIC EDUCATION - Galan, Yaroslav; Beshlei, Olga (Young Scientist, 2021)
National-patriotic education of children and schoolchildren remains relevant today. Scholars claim that the formation of universal, humanistic spiritual and moral values is greatly influenced by the ideals of Olympism. With the help of Olympic education, it is possible to form the patriotic consciousness of modern children, in particular schoolchildren. In addition, Olympic education fulfils a number of tasks aimed at educating children and schoolchildren, namely their awareness of patriotic values, cultural and historical past of Ukraine, gaining patriotic experience, fostering a sense of respect, loyalty to homeland, responsibility for the honour of the state. The purpose of the study is to carry out the survey among teach-ers, which aims to identify the main trends in the implementation of innovative forms and dissemination of Olympic values in the context of patriotic education. To achieve this goal during the study, we used a set of research methods that complement each other. These include the elaboration and generalization of scientific and methodological literature, sociological surveys and statistical methods. A sociological survey was conducted among teachers online in 2021 through Google forms. The teachers took part in the webinar called “Innovative forms of teaching physical education in the modern school”. The total number of respond-ents comprised 76 people. Results. The study estimated teachers’ competence in implementing innovative forms of Olympic education in the context of patriotic education. According to the expert survey, 69.7 % of teachers introduced innovative forms in the process of physical education of schoolchildren, 28.9 % – did so in part, and only 1.3 % did not implement at all. As our research has shown, the majority of experts in the field require the improvement of the material and technical base; a significant number of staff need to improve their knowledge on this topic, including methodological advice, courses, webinars, seminars, theo-retical and practical classes; there is a need for demonstrative activities; it is necessary to provide modern literature on Olympic education and teaching innovative forms. Moreover, the issue of distance learning was discussed separately, as there was the need to collect information on this topic, which will allow teach-ers to become more competent. The obtained results show that there is a significant challenge in the lack of proper sports equipment.
Keywords: Olympic education, patriotism, pedagogical workers, innovative forms, children, expert survey